2021
DOI: 10.1186/s12889-021-10183-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid review of COVID-19 epidemic estimation studies for Iran

Abstract: Background To inform researchers about the methodology and results of epidemic estimation studies performed for COVID-19 epidemic in Iran, we aimed to perform a rapid review. Methods We searched for and included published articles, preprint manuscripts and reports that estimated numbers of cumulative or daily deaths or cases of COVID-19 in Iran. We found 131 studies and included 29 of them. Results The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…MGEs cover different types of event and contexts such as public and private celebrations, festivals, religious events and pilgrimages, sporting and touristic events, and political meetings. The crucial role of MGEs in the global propagation of the disease has been evidenced in several countries, including China [ 3 ], Iran [ 4 ], Malaysia [ 5 ], Italy [ 6 ], Spain [ 7 ], France [ 8 ], Germany [ 9 ], Jordan [ 10 ], Malta [ 11 ], Switzerland [ 12 ], and Malawi [ 13 ]. Significant international efforts have been made to implement specific measures, risk assessment and surveillance, and event cancellations in order to prevent the spread of SARS-CoV-2 from MGEs [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…MGEs cover different types of event and contexts such as public and private celebrations, festivals, religious events and pilgrimages, sporting and touristic events, and political meetings. The crucial role of MGEs in the global propagation of the disease has been evidenced in several countries, including China [ 3 ], Iran [ 4 ], Malaysia [ 5 ], Italy [ 6 ], Spain [ 7 ], France [ 8 ], Germany [ 9 ], Jordan [ 10 ], Malta [ 11 ], Switzerland [ 12 ], and Malawi [ 13 ]. Significant international efforts have been made to implement specific measures, risk assessment and surveillance, and event cancellations in order to prevent the spread of SARS-CoV-2 from MGEs [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Epidemic estimation studies for Iran claim that the exact number of daily deaths or cases of COVID-19 is much greater than those in Iran's official reports. 7 Following COVID-19 restrictions in Iran, the collapse of economic activity and financial markets began. The government entered an economic crisis alongside the U.S.-imposed embargo.…”
Section: The Covid-19 Health Crisismentioning
confidence: 99%
“…Eligibility criteria: Eligibility criteria for the target COVID-19 models to be included are (1) an international model scope, and (2) periodic updates. "International model" denotes a model that estimates COVID-19 cases or infections and deaths for all countries of the world, with global-level estimates that equate the sum of the national-level estimates.…”
Section: Objectivementioning
confidence: 99%
“…Finding the eligible models: The eligible models were found within the literature search of a previously publication, "Rapid review of COVID-19 epidemic estimation studies for Iran" [1], and the results were veri ed by comparison with models found in a recently published study on "Predictive performance of international COVID-19 mortality forecasting models" [2]. While non-updating or one-time models can be contemporaneously useful, their results would not sustain up-to-dateness in the long run, especially with emergence of new variants of concern and various degrees of uncertainties in progression of vaccination coverage.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation